Validation of a Self-Directed Learning Instrument in Blended Learning: Evidence from Undergraduate Students - Chantelle Bosch (Journal of Educational Science and Technology (EST), 2026)
Self-directed learning (SDL) is a critical competency in blended learning environments, where students are expected to assume greater responsibility for managing their own learning processes. Although the Self-Directed Learning Instrument (SDLI) has been validated in various educational settings, limited evidence exists regarding its structural validity within intervention-based blended learning environments characterised by cooperative learning and increased learner autonomy. This study therefore aimed to validate the SDLI within a cooperative blended learning context. A quantitative research approach was employed using pooled survey data collected from undergraduate students (n = 530) enrolled in a blended learning economics module at a South African university over two academic years. The broader study followed a quasi-experimental design investigating the implementation of cooperative learning to enhance self-directed learning. Confirmatory factor analysis (CFA) was conducted to assess construct validity, while Cronbach’s alpha coefficients were calculated to determine internal consistency. The findings supported the four-factor structure of the SDLI, with all factor loadings being statistically significant (p < 0.001) and ranging from 0.388 to 0.762. The model demonstrated adequate fit (CFI = 0.911; RMSEA = 0.062), while reliability analysis indicated satisfactory internal consistency across the subscales (α = 0.706–0.816). The results confirm that the SDLI is a valid and reliable instrument for measuring SDL within cooperative blended learning environments. This study extends previous SDLI validation research by demonstrating the applicability of the instrument within a pedagogically designed blended learning intervention characterised by collaborative and self-directed learning processes.